Positive allosteric modulators of α7* or β2* nicotinic acetylcholine receptors trigger different kinase pathways in mitochondria. (June 2018) - Uspenska, Kateryna; Lykhmus, Olena; Arias, Hugo R.; Pons, Stephanie; Maskos, Uwe; Komisarenko, Serghiy; Skok, Maryna
Highlights: Mitochondrial α7 nAChR signaling is stimulated by type II, but not type I, PAMs. Binding to orthosteric and transmembrane, but not vestibular, sites triggers signaling. The α7 and β2 nAChR subunits are responsible for engaging different kinases. Multiple heteromeric nAChR subtypes ensure mitochondria resistance to apoptogenic agents. Abstract: Mitochondrial nicotinic acetylcholine receptors (nAChRs) regulate the early stage of mitochondria-driven apoptosis, including cytochrome c release. Mitochondrial nAChR signaling is mainly mediated by intra-mitochondrial kinases, in an ion-independent manner. To determine the relationship between specific nAChR subtypes and mitochondrial kinases, the effects of a set of nAChR subtype-selective positive allosteric modulators (PAMs) on cytochrome c release from mouse liver mitochondria stimulated by 0.9 μM Ca 2+, 0.5 mM H2 O2 or 1.0 μM wortmanin is studied. The results indicate that Ca 2+ -stimulated cytochrome c release from wild-type, but not α7-/-, mice mitochondria is attenuated by the potent agonist PNU-282987 or type II PAMs (PNU-120596, 4BP-TQS, and PAM-2-4), but not by NS-1738, a type I PAM. In contrast, wortmannin-stimulated cytochrome c release from wild-type and, to a lesser extent, α7-/- mice mitochondria is efficiently attenuated by the β2-selective PAM desformylfrustrabromine. In conclusion, the ligand-evoked α7* nAChR conformational changes required to induce intra-mitochondrial signaling can be triggered through orthosteric (agonists) and transmembrane (type II PAMs) sites, but not by the interaction with type I PAMs. The α7 and β2 nAChR subunits are responsible for the engagement of distinct kinase pathways, supporting the concept that multiple heteromeric nAChR subtypes ensure mitochondria resistance to various exogenous and endogenous apoptogenic agents.